Development of coconut pith chars towards high elemental mercury adsorption performance - Effect of pyrolysis temperatures - Johari, K. (Elsevier Ltd, 2016)
In this study, chars from coconut pith (CP) were prepared aiming for superior adsorption towards elemental mercury (Hgo). The yield, proximate analysis, textural characteristics, surface functional groups and elemental composition analyses of the chars produced at pyrolysis temperature of 300 °C, 500 °C, 700 °C and 900 °C were compared. The surface area, pore volume, ash and carbon content of chars increased, while the yield and moisture content decreased with increasing pyrolysis temperatures. The changing of physical and chemical properties of the chars produced at variety pyrolysis temperature was much effect on the Hgo adsorption performance and definitely provides important information on the Hgo adsorption mechanism. The highest Hgo adsorption capacity was observed for CP900 (6067.49 μg/g), followed by CP700 (2395.98 μg/g), CP500 (289.76 μg/g), CP300 (1.68 μg/g), and CP (0.73 μg/g). The equilibrium data were well described by the Freundlich adsorption isotherm model. The pseudo-second order best described the kinetic data of the Hgo adsorption onto CP and CP300. For chars produced at higher pyrolysis temperature, however, the pseudo-zero order and pseudo-second order fitted well for the adsorption and breakthrough regions, respectively. The Hgo adsorption capacity of chars obtained from high pyrolysis temperature of CP significantly outperformed the commercial activated carbon (Darco KB-B) as well as superior to chars reported in the literature indicating the CP can be used as a precursor for preparation of chars as elemental mercury adsorbents. © 2016 Elsevier Ltd.